Penanaman Nilai Spiritual dalam Dimensi Psikoterapi Islam di PP. Rehabilitasi Salafiyah Syafi’iyah Nashrun Minallah - Alawiyah, Desi; Handayani, Iin (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
The search for meaning of life can be achieved by using the dimension of spirituality to fulfill the inner needs of humans. This study was intended to describe the spiritual values instilled by the coaches of Nashrun Minallah Islamic Boarding School to students who experienced mental disorders, especially those affected by magic and genie disorders through Islamic psychotherapy. This article uses a type of qualitative research, the method of collecting data through observation, interviews and documentation, with analytical techniques using data reduction, presentation of data and drawing conclusions. The results of the study that the spiritual form shown by santri leads to positive spiritual products includes a more meaningful life, more active worship and a balance between fulfilling life in the world and in the hereafter according to the guidance of the Qur'an and as-Sunnah. The form of Islamic psychotherapy that is practiced is the therapy of prayer, dhikr and ruqyah so that someone is spared from interference from spirits.